Penyelundupan dan Perdagangan Barang Ilegal di Wilayah Perbatasan Indonesia-Filipina - Nento, Ridwan; Niode, Burhan; Waworundeng, Welly (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2024)
Smuggling and trade of illegal goods in the Indonesia-Philippines border continues to this day. This study aimed to discern the routes and methods used for those illegal activities and identify the types of goods smuggled and traded from the Philippines to Indonesia from a transnational organized crime perspective. This study used a descriptive qualitative method. Data were obtained using the following techniques: in-depth interviews, observations, literary studies, and comparison of field findings with theoretical frameworks. The results suggested three main routes for smuggling and illegal trading. The operation is carried out disguised as fishermen bartering fishery products using small, modified boats such as pump boats, supported by information from existing smuggling networks on the land. The smuggled goods are identified as fighting roosters, vitamins and medications for roosters, ethyl alcohol-containing beverages/MMEA, cosmetics, plywood, and firearms.